The ectomycorrhizal basidiomycete Laccaria bicolor releases a secreted β‐1, 4 endoglucanase that plays a key role in symbiosis development. Issue 4 (6th April 2018) - Zhang, Feng; Anasontzis, George E.; Labourel, Aurore; Champion, Charlotte; Haon, Mireille; Kemppainen, Minna; Commun, Carine; Deveau, Aurélie; Pardo, Alejandro; Veneault‐Fourrey, Claire; Kohler, Annegret; Rosso, Marie‐Noëlle; et al.
Summary: In ectomycorrhiza, root ingress and colonization of the apoplast by colonizing hyphae is thought to rely mainly on the mechanical force that results from hyphal tip growth, but this could be enhanced by secretion of cell‐wall‐degrading enzymes, which have not yet been identified. The sole cellulose‐binding module (CBM1) encoded in the genome of the ectomycorrhizal Laccaria bicolor is linked to a glycoside hydrolase family 5 (GH5) endoglucanase, LbGH5‐CBM1. Here, we characterize LbGH5‐CBM1 gene expression and the biochemical properties of its protein product. We also immunolocalized LbGH5‐CBM1 by immunofluorescence confocal microscopy in poplar ectomycorrhiza. We show that LbGH5‐CBM1 expression is substantially induced in ectomycorrhiza, and RNAi mutants with a decreased LbGH5‐CBM1 expression have a lower ability to form ectomycorrhiza, suggesting a key role in symbiosis. Recombinant LbGH5‐CBM1 displays its highest activity towards cellulose and galactomannans, but no activity toward L. bicolor cell walls. In situ localization of LbGH5‐CBM1 in ectomycorrhiza reveals that the endoglucanase accumulates at the periphery of hyphae forming the Hartig net and the mantle. Our data suggest that the symbiosis‐induced endoglucanase LbGH5‐CBM1 is an enzymatic effector involved in cell wall remodeling during formation of the Hartig net and is an important determinant for successful symbiotic colonization.